2
$\begingroup$

The number of integer solutions of the following equation

$(x \leq y)$

$xy -6(x+y) = 0$

I have concluded that $xy$ is a multiple of $6$ and that $x$ is negative and $y$ is positive.

After that, I obtained these solutions with trial and error: $(-3,2) , (-6,3), (-12,4), (-18,4)$.

Now the obvious question is how long do I continue? And isn't there any better process than this clumsy mess?

And @Dhruv in the comments below proves my analysis wrong as well.

$\endgroup$
  • 2
    $\begingroup$ $(x-6)(y-6)=36$. $\endgroup$ – almagest Mar 26 '16 at 13:15
  • $\begingroup$ Are you sure $(-18, 4)$ is a solution? $\endgroup$ – TheRandomGuy Mar 27 '16 at 6:22
  • $\begingroup$ Ciuld you explain why you reasoned that $x$ is negative and $y$ is positive? $\endgroup$ – TheRandomGuy Mar 27 '16 at 6:25
  • 1
    $\begingroup$ What about the solution $(12, 12)$? $\endgroup$ – TheRandomGuy Mar 27 '16 at 6:26
  • $\begingroup$ @Druv I agree that my analysis is wrong. Appreciate it if you could further point me in the right direction. $\endgroup$ – smkj33 Mar 28 '16 at 14:39
1
$\begingroup$

This was a fun question, thank you :)

First you factor using Simon's favorite factoring trick (explanation below):

Multiplying out $$xy-6(x+y)=0,$$ you get:
$$xy-6x-6y=0.$$

Adding $-6\cdot-6=36$ to both sides, you end up with: $$xy-6x-6y+36=36\implies (x-6)(y-6)=36.$$ Now factor $36$ for the posisble values of $(x-6)$ and $(y-6)$.

Hint: $36$ can be broken up as $1\cdot36$, $2\cdot18$, $3\cdot12$, $4\cdot9$, and $6\cdot6$ (and their negative counterparts).

Another hint: since $x\leq y$, we know that $(x-6)\le(y-6)$.

Another hint: plug in the factors of $36$ for $(x-6)$ and $(y-6)$:
$(x-6)(y-6)=36$
$(1)(36)=36$
$(2)(18)=36$
$(3)(12)=36$
$(4)(9)=36$
$(6)(6)=36$
$(-36)(-1)=36$
$(-18)(-2)=36$
$(-12)(-3)=36$
$(-9)(-4)=36$
$(-6)(-6)=36$

Solution: We count the amount of listings above to get our answer $\boxed{10}.$
If we want the individual values of $x$ and $y$, we plug them into the equations above, for example, for $(-9)(-4)$, we would do:
$x-6=-9\implies x=-3$ and $y-6=-4\implies y=2$.
However, your assumption about a positive $y$ and negative $x$ is false. For example, for $(6)(6)$, we get $x=y=0$, where neither $y$ is positive nor $x$ is negative.

Hope this helps :)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.